Credit Disposement and Its Internal Determinants - ledy gita septiyani (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
The purpose of this research was to find out the effect of third-party funds, capital adequacy ratio, loan to deposit ratio, return on assets, non-performing loan and operating expense ratio on credit disposementof PD BPR BKK Purbalingga It needs to be explored more deeply about the effect of these variables on credit disposementto get more complete evidence. The data in this study were quarterly financial reports of PD BPR BKK Purbalingga during the period of 2011-2018. Data anaysis method used was multiple regression method using SPSS 24. Based on the data analysis, it can be concluded that (1)Third-party funds have positive effect on credit disposementof PD BPR BKK Purbalingga, (2)Capital adequacy ratio has positive effect on credit disposement of PD BPR BKK Purbalingga, (3)Loan to deposit ratio has positive effect on credit disposementof PD BPR BKK Purbalingga, (4)Return on assets does not have positive effect on credit disposementof PD BPR BKK Purbalingga, (5)Non-performing loan does not have negative effect on credit disposementof PD BPR BKK Purbalingga, (6)Operational expense ratio has negative effect on credit disposement of PD BPR BKK Purbalingga.